SAT0343 NUTRITIONAL STATUS OF SYSTEMIC SCLEROSIS PATIENTS: A PILOT STUDY. (2nd June 2020) - Szabo, I.; Petcu, A.; Chicinas, D.; Rednic, V.; Tamas, M. M.; Muntean, L.; Filipescu, I.; Simon, S. P.; Pamfil, C.; Rednic, S.
Abstract : Background: Gastrointestinal involvement (GI) in systemic sclerosis (SSc) is one of the major disease burdens. Its consequences on the nutritional status of SSc patients and their quality of life is poorly evaluated during routine check-ups. Since malnutrition is an important cause of morbidity and mortality, addressing this issue seems necessary. Objectives: The aim of this study was to evaluate the risk of malnutrition in SSc patients and to identify potential associations between the risk of malnutrition and clinical features or laboratory parameters. Methods: All patients aged >18 years old with a definite diagnosis of SSc according to the 2013 ACR/EULAR classification criteria from the EUSTAR Center 16 and ERN ReCONNET cohort of the County Emergency Clinical Hospital Cluj-Napoca were included in the study. Patients with localized scleroderma, scleroderma sine scleroderma, overlap syndromes and mixed connective tissue disease were excluded. Clinical and laboratory data was collected from the EUSTAR database and medical charts. A telephone survey was conducted and patients were interviewed using the Malnutrition Universal Screening Tool (MUST) questionnaire. Results: 75 patients were eligible for the study. Female to male ratio was 10:1 with an almost equal distribution among limited (57%) and diffuse (43%) SSc subtypes. The most prevalent autoantibodies were anti-TOPO-I and anti-centromere. GI symptoms were reported in 48.6% patients out of which 86% SSc patients underwent further evaluation by upper GI endoscopy. Abnormal endoscopic findings, such as esophagitis, Barret esophagus and gastritis were identified in 80% patients. Most patients had a low risk of malnutrition (93%) with only a minority carrying a medium (6%) or high (1%) risk. No significant association was demonstrated between MUST score and the extend of cutaneous involvement (limited SSc versus diffuse SSc; p=0.39), presence of GI symptoms (p=0.35), presence of abnormal endoscopic findings (p=0.45) or presence of anemia (p=0.83). Conclusion: The majority of SSc patients from this cohort exhibited a low risk of malnutrition. These results are contradictory to previous literature reports. A possible explanation is that the MUST score is a dynamic screening tool and therefore interviewing patients with a stable disease (outpatient care) versus patients with active disease (inpatient care) might lead to different results. Another limitation of this study is the small number of patients included. This is a pilot study. We aim to further extend the study population to the other EUSTAR cohorts and to prospectively evaluate these patients in an inpatient care setting. References: [1]Dupont R et al. Impact of micronutrient deficiency & malnutrition in systemic sclerosis: Cohort study and literature review. Autoimmun Rev. 2018 Nov;17(11):1081-1089; [2]Caimmi C et al. Malnutrition and sarcopenia in a large cohort of patients with systemic sclerosis. Clin Rheumatol. 2018 Apr;37(4):987-997; [3]Türk İ et al. Malnutrition, associated clinical factors, and depression in systemic sclerosis: a cross-sectional study. Clin Rheumatol. 2020 Jan;39(1):57-67. Disclosure of Interests: None declared